Respiratory muscle dysfunction in congestive heart failure: the role of pulmonary hypertension - Filusch, Arthur; Ewert, Ralf; Altesellmeier, Maike; Zugck, Christian; Hetzer, Roland; Borst, Mathias M.; Katus, Hugo; Meyer, Franz Joachim (International journal of cardiology, 2011)
Background - Inspiratory muscle weakness has been described in patients with congestive heart failure (CHF), and only recently in patients with idiopathic pulmonary arterial hypertension. However, the relationship between pulmonary hemodynamics and respiratory muscle function has not been investigated in patients with CHF. - Methods and results - In two tertial referral centers for CHF patients, 532 consecutive CHF patients (159 female, age 59±12years, NYHA I-IV) were studied by right heart catheterization, maximal inspiratory mouth occlusion pressure (Pimax) and pressure 0.1s after beginning of inspiration during tidal breathing at rest (P0.1). There was a significant correlation between Pimax and mean pulmonary artery pressure (PAPm) (r=−0.65, p=0.0023), mean pulmonary capillary wedge pressure (PCWPm) (r=−0.56; p=0.0018), PVR (r=−0.73; p=0.0031), and cardiac output (r=0.51; p=0.0022). Moreover, the ratio P0.1/Pimax showed a linear correlation with PAPm (r=0.54; p=0.0019), and with TPG (r=0.64; p=0.0014) respectively. Vital capacity was reduced in relation to increased PAPm (r=−0.54; p=0.0029). Pimax and P0.1/Pimax were independent from VC. - Conclusions - This study provides the first evidence of a close relation between inspiratory muscle dysfunction, increased ventilatory drive and pulmonary hypertension in a large patient cohort with CHF. Pimax and P0.1 can easily be measured in clinical routine and might become an additional parameter for the non-invasive monitoring of the hemodynamic severity of disease.
Online verfügbar: 4 Mai 2010
Gesehen am 03.11.2022